Вплив покриваючого ліганду на величину щілини та енергетичні рівні екситонів колоїдних розчинів та плівок квантових точок ZnSe - Bondar, N. V.; Brodyn, M. S.; Tverdokhlibova, O. V.; Matveevskaya, N. A.; Beynik, T. G. (Publishing house "Academperiodika", 2019)
Semiconductor quantum dots are promising nanostructures for their application in solar cells of the 3rd generation, photodetectors, light emitting diodes, and as biological markers. However, the issue concerning the influence of superficial organic stabilizers (ligands) on the energy of excitons in quantum dots still remains open. In this work, by analyzing the optical spectra of colloidal solutions and films of ZnSe quantum dots stabilized with 1-thioglycerol, it is found that the energy of excitons and their migration depend not only on the quantum confinement effect, but also on the superficial contribution from the thiol stabilizer group –SH. The dependence of the exciton energy in ZnSe quantum dots on the surface stabilizer concentration is experimentally revealed for the first time. The short size of the stabilizer molecular chain and the large initial energy of excitons are shown to result in the effective migration of excitons over an array of quantum dots.